TINJAUAN YURIDIS MENGENAI PENERAPAN HAK MENDAHULU (PREFEREN) DALAM PENAGIHAN UTANG PAJAK PADA KASUS KEPAILITAN (Studi Kasus Putusan Mahkamah Agung Nomor 168 PK/Pdt.Sus/2012) - Putri Kemala Sari (Prodi Ilmu Hukum, Universitas Teuku Umar, 2018)
Taxes are a compulsory contribution to a country that is indebted by an individual or a coercive body under the Act with no direct remuneration and used for the purposes of the state for the greatest possible prosperity of the people. The provision indicates that the position of the state or in other words referred to as the fiscal gets a very special place to regulate all arrangements concerning taxation and this is also marked by the nature of the inherent force to the taxpayer to pay off the tax debt. As regulated in Law Number 16 Year 2009 (hereinafter referred to as UU KUP), Article 21 paragraph (1) which reads